2005
DOI: 10.1038/sj.bmt.1705112
|View full text |Cite
|
Sign up to set email alerts
|

Autologous transplantation for primary systemic AL amyloidosis is feasible outside a major amyloidosis referral centre: the Calgary BMT Program experience

Abstract: Summary:Recent reports from large amyloidosis referral centers suggest that primary systemic AL amyloidosis patients treated with high-dose melphalan (HDM) and autologous stem cell transplantation (ASCT) survive longer than historical controls treated with less intensive chemotherapy, despite high transplant-related mortality (TRM) rates of 410%. A retrospective review was conducted to determine if the outcome of ASCT for AL amyloidosis at our institution was similar to that reported at major amyloidosis refer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…In our cohort of 270 patients, the mortality rate on day 100 was 11%; this compares favorably with other institutions that reported mortality rates as high as 40% [11][12][13]. A low mortality rate is necessary to compare stem cell transplantation with conventional chemotherapy when using survival as an endpoint.…”
Section: Outcome After Transplantationsupporting
confidence: 67%
“…In our cohort of 270 patients, the mortality rate on day 100 was 11%; this compares favorably with other institutions that reported mortality rates as high as 40% [11][12][13]. A low mortality rate is necessary to compare stem cell transplantation with conventional chemotherapy when using survival as an endpoint.…”
Section: Outcome After Transplantationsupporting
confidence: 67%
“…Untreated, the prognosis of patients with advanced amyloidosis is grim. Treatment with high-dose chemotherapy and HCT may reverse the amyloid-related disease (Skinner et al, 2004;Chow et al, 2005), however, the benefit of HCT is still controversial (Jaccard et al, 2007;Kumar et al, 2008). Compared to multiple myeloma, where the transplant-related mortality is <2%, mortality rates for transplantation in patients with amyloidosis ranges from 11% to 25%.…”
Section: Disease-related Consequencesmentioning
confidence: 99%
“…6 Single and multicenter studies show CR rates of 16%-67%, organ responses in 25%-45% of patients, and a median overall survival (OS) of Ďł 5 years. [7][8][9][10][11][12][13][14][15][16] A case-control study demonstrated the benefit of this procedure for patients younger than 70 years compared with nontransplant regimens, most of them alkylator-based oral chemotherapy. 17 A major issue in HDM/SCT for AL amyloidosis is the potential for high treatment-related mortality (TRM) because of underlying organ dysfunction in this disease.…”
Section: Introductionmentioning
confidence: 99%